Metric Characteristics of the Scale of Attitudes towards Persons with Disabilities (SAPD) - Sainz-Palafox, Miguel Angel; Vera-Noriega, José Ángel; Tánori-Quintana, Jesús; Sainz-Palafox, Miguel Angel; Vera-Noriega, José Ángel; Tánori-Quintana, Jesús (Instituto de Investigaciones Psicológicas (IIPSI, Conicet-UNC), 2022)
Due to the relevance in the understanding of the role of attitudes towards people with disability in the inclusive education process, numerous psychometric tools have been developed. In the Spanish-speaking context, the Scale of Attitudes towards People with Disabilities (SAPD) stands out. However, its validity has not been demonstrated yet on the Mexican population. For this reason, this work aims at evaluating the validity evidence of the SAPD and proposing a modified version in a sample of 1934 higher educationstudents from Sonora, Mexico. An exploratory and confirmatory factor analysis, as well as a Rasch and invariance analysis were carried out. Results show that the modified version has appropriate psychometric properties and a bifactorial structure with egalitarian and discriminatory attitudes about disability.